2021
DOI: 10.3390/ijms222212594
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Myotonic Dystrophies: A Minireview

Abstract: Myotonic dystrophy type 1 and 2 (DM1 and DM2) are two multisystemic autosomal dominant disorders with clinical and genetic similarities. The prevailing paradigm for DMs is that they are mediated by an in trans toxic RNA mechanism, triggered by untranslated CTG and CCTG repeat expansions in the DMPK and CNBP genes for DM1 and DM2, respectively. Nevertheless, increasing evidences suggest that epigenetics can also play a role in the pathogenesis of both diseases. In this review, we discuss the available informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Given their previously known significance in human disease, DNA methylation (DNAme) and regulatory microRNA (miRNA) profiles are suitable for characterization in DM1 by means of whole-genome epigenomics experimental strategies. To date, DNAme omics studies in DM1 have focused only on CpG islands surrounding the CTG repeat [69], mainly approached using pyrosequencing omics methodology.Accumulating evidence supports that hypermethylation levels are associated with DM1 pathogenesis, with different tissues and clinical forms being affected [69]. Only one genome-wide methylation study has been performed in DM1, involving also several other trinucleotide repeat disorders.…”
Section: Other Omics Studies In Dm1mentioning
confidence: 99%
“…Given their previously known significance in human disease, DNA methylation (DNAme) and regulatory microRNA (miRNA) profiles are suitable for characterization in DM1 by means of whole-genome epigenomics experimental strategies. To date, DNAme omics studies in DM1 have focused only on CpG islands surrounding the CTG repeat [69], mainly approached using pyrosequencing omics methodology.Accumulating evidence supports that hypermethylation levels are associated with DM1 pathogenesis, with different tissues and clinical forms being affected [69]. Only one genome-wide methylation study has been performed in DM1, involving also several other trinucleotide repeat disorders.…”
Section: Other Omics Studies In Dm1mentioning
confidence: 99%
“…This has been well-characterized in congenital DM1 with the role of DNA hypermethylation at the CTCF1 binding site, which was discussed above in the genetics section of this review article. A recent review article summarizes available evidence on the potential role of epigenetics in DM1 and DM2 [ 82 ]. DNA methylation upstream of the CTG repeats in blood DNA has been proposed as a marker of maternally inherited congenital DM1 [ 25 , 49 ].…”
Section: Postulated Pathomechanismsmentioning
confidence: 99%
“…The CTCF protein function as transcriptional activator or repressor but also as an insulator protein [ 46 , 47 , 97 , 98 ]. In DM1, the absence of CTCF binding due to CpG methylation, induces the loss of its insulator activity, eventually allowing the propagation of heterochromatin and thus the downregulation of DMPK and SIX5 genes for more details, see the review [ 99 ]. Recently, Yanovsky-Dagan et al identified a CpG-rich region, 650 bp upstream of the repeat, as an enhancer of SIX5 [ 100 ].…”
Section: Epigenetics Gene Expression and Chromatin At The Dm1 Locusmentioning
confidence: 99%